2010
DOI: 10.1016/j.otohns.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Nasopharyngeal Bacterial Flora after Adenoidectomy in Children: A Systematic Review

Abstract: Adenoidectomy seems to have a beneficial effect on the nasopharyngeal bacterial flora. Because the overall quality of the available evidence is low, it is important that controlled studies are initiated into the short- and long-term effect of adenoidectomy on the nasopharyngeal bacterial flora and its relationship with the recurrence of URTIs in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Corroborated by published data (26–29), our results support the involvement of these microorganisms in the pathogenesis of recurrent tonsillitis and rhinopharyngitis.…”
Section: Discussionsupporting
confidence: 88%
“…Corroborated by published data (26–29), our results support the involvement of these microorganisms in the pathogenesis of recurrent tonsillitis and rhinopharyngitis.…”
Section: Discussionsupporting
confidence: 88%
“…Infections cause by drug resistant pathogens in the nasopharynx or the adenoids seems to be harder to treat medically, which could result in the need for adenoidectomy, which seems to have a beneficial effect on the nasopharyngeal bacterial flora [28]. Aarts et al [28] demonstrated that S. pneumoniae and H. influenza were most often detected in the nasopharynx of children with recurrent URTIs, and carriage of these bacteria decreased after adenoidectomy in the majority of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Aarts et al [28] demonstrated that S. pneumoniae and H. influenza were most often detected in the nasopharynx of children with recurrent URTIs, and carriage of these bacteria decreased after adenoidectomy in the majority of studies.…”
Section: Discussionmentioning
confidence: 99%
“…[27] In a review, adenoidectomy was suggested to have a beneficial effect on the nasopharyngeal bacterial flora, causing a decrease in the load of potential pathogens, specifically Streptococcus pneumoniae and Haemophilus influenzae, and helping reestablishment of normal non-pathogenic flora. [28] Obstructive sleep apnea syndrome (OSAS) and sleep disordered breathing (SDB) are important indications for adenoidectomy. Pediatric OSA affects 2-3% of children.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%